2008
DOI: 10.1016/j.fuel.2007.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Flash co-pyrolysis of biomass with polylactic acid. Part 1: Influence on bio-oil yield and heating value

Abstract: High amounts of water present in bio-oil are one of the major drawbacks for its utilisation as a fuel. One technology that shows the potential to satisfy the demand for bio-oil with a reduced water content is the flash co-pyrolysis of biomass with polylactic acid, PLA. The influence of PLA on the pyrolysis of willow is investigated with a semi-continuous home-built pyrolysis reactor. Flash co-pyrolysis of willow/PLA blends (10:1, 3:1, 1:1 and 1:2) show synergetic interaction. A higher bio-oil yield and a lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 120 publications
(69 citation statements)
references
References 20 publications
3
61
0
1
Order By: Relevance
“…The water content for bio-oil obtained by pyrolysis of AKP sludge is 10.3%, for OLDA sludge 17.0%. These values are significantly lower than the water content of bio-oils obtained from pyrolysis of other biomasses which ranges between 20 and 40% [11,13].…”
Section: Pyrolysis Products -General Featuresmentioning
confidence: 68%
See 1 more Smart Citation
“…The water content for bio-oil obtained by pyrolysis of AKP sludge is 10.3%, for OLDA sludge 17.0%. These values are significantly lower than the water content of bio-oils obtained from pyrolysis of other biomasses which ranges between 20 and 40% [11,13].…”
Section: Pyrolysis Products -General Featuresmentioning
confidence: 68%
“…The flash pyrolysis was performed in semi-continuous lab scale reactor consisting of three parts: the vertical reactor, the injection and the recuperation system [13].…”
Section: Experimental Apparatus and Proceduresmentioning
confidence: 99%
“…TGA, TG/MS and TG/FT-IR) did not result in any conclusive evidence regarding interactions between willow and PHB during (slow) co-pyrolysis, nor regarding a decrease in the amount of pyrolytic water in the evolving gasses (as was observed for the co-pyrolysis of willow and PLA in earlier research [13]), a synergetic reduction of the water content and of the amount of pyrolytic water produced during the flash co-pyrolysis of willow and PHB with the semicontinuous home-built pyrolysis reactor is achieved. Additionally, a synergetic increase in pyrolysis yield, water-free bio-oil yield and energy recuperation is observed.…”
Section: Flash (Co-)pyrolysismentioning
confidence: 60%
“…The CHNS-and O-content of the input materials are determined via two distinct experiments, using a For a detailed description of the experimental flash pyrolysis set-up and procedure, refer to [13]. 1 To the knowledge of the authors, the occurrence of crystals in bio-oil has never been reported.…”
Section: Ultimate Analysismentioning
confidence: 99%
See 1 more Smart Citation